Smiling Faces of Delhi. Issue 2 (December 2017) - Captions, David Goldman; Kaur, Jasneet
This photo essay carries pictures of children, women and men from certain freed/denotified tribes (DNTs) living in the National Capital Territory of Delhi, trying to carve an existence for themselves. The idea is to capture the smiling faces of these children, women and men who are around us every single day, visible yet invisible.